Second death : theatricalities of the soul in Shakespeare's drama - Sherman, Donovan (Edinburgh critical studies in Shakespeare and philosophy., 2016)
Second Death seeks to revitalise our understanding of the soul as a philosophically profound, theoretically radical, and ultimatelý⁰₄and counterintuitivelý⁰₄theatrically realised concept. The book contends that the work of Shakespeare, when closely read alongside early modern cultural and religious writings, helps us understand the souĺ⁰₉s historical placement as a powerful paradox: it was essential to establishing humanity but resistant to clear representation. Drawing from current critical theory as well as extensive historical research, Second Death examines works of Shakespearean drama, including The Merchant of Venice, Coriolanus, and The Winteŕ⁰₉s Tale, to suggest that rather than simply being incapable of understanding or physical realisation, the soul expressed itself in complex and subtle modes of performance. As a result, this book offers new ways of looking at identity, theatre, and spirituality in Shakespearé⁰₉s era and in our own.